Formation and three-dimensional architecture of Leishmania adhesion in the sand fly vector - Yanase, Ryuji; Moreira-Leite, Flávia; Rea, Edward; Wilburn, Lauren; Sádlová, Jovana; Vojtkova, Barbora; Pružinová, Katerina; Taniguchi, Atsushi; Nonaka, Shigenori; Volf, Petr; Sunter, Jack D (eLife, 2023)
Attachment to a substrate to maintain position in a specific ecological niche is a common strategy across biology, especially for eukaryotic parasites. During development in the sand fly vector, the eukaryotic parasite Leishmania adheres to the stomodeal valve, as the specialised haptomonad form. Dissection of haptomonad adhesion is a critical step for understanding the complete life cycle of Leishmania. Nevertheless, haptomonad studies are limited, as this is a technically challenging life cycle form to investigate. Here, we have combined three-dimensional electron microscopy approaches, including serial block face scanning electron microscopy (SBFSEM) and serial tomography to dissect the organisation and architecture of haptomonads in the sand fly. We showed that the attachment plaque contains distinct structural elements. Using time-lapse light microscopy of in vitro haptomonad-like cells, we identified five stages of haptomonad-like cell differentiation, and showed that calcium is necessary for Leishmania adhesion to the surface in vitro. This study provides the structural and regulatory foundations of Leishmania adhesion, which are critical for a holistic understanding of the Leishmania life cycle.
Keywords: serial block face scanning electron microscopy; Microscopy, Electron; host-parasite interaction; Psychodidae; cell adhesion; elektronová mikroskopie; serial section electron microscopy tomography; cell biology; zvířata; infectious disease; microbiology; sand fly; Leishmania; Animals